2023
DOI: 10.1021/acsomega.3c01153
|View full text |Cite
|
Sign up to set email alerts
|

Design-of-Experiment-Assisted Fabrication of Biodegradable Polymeric Nanoparticles: In Vitro Characterization, Biological Activity, and In Vivo Assessment

Mushtaq Ahmad Mir,
Md Habban Akhter,
Obaid Afzal
et al.

Abstract: Berberine (BER) is an alkaloid obtained from berberis plant having broad biological activities including anticancer. BER-encapsulated alginate (ALG)/chitosan (CHS) nanoparticles (BER–ALG/CHS-NPs) were developed for long-acting improved treatment in breast cancer. The surface of the NPs was activated by a conjugation reaction, and thereafter, the BER–ALG/CHS-NP surface was grafted with folic acid (BER–ALG/CHS-NPs–F) for specific targeting in breast cancer. BER–ALG/CHS-NPs–F was optimized by applying the Box–Beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In the same experimental setup, free BBR inhibited both planktonic and sessile populations, although at significantly higher levels, i.e., ≥125 μg/mL, compared to that accomplished by the BBR-loaded nanoparticles. The need of higher doses of free BBR might suggest the relevance of antibacterial surface-mediated mechanisms as observed before [ 63 ] which may be further supported by the low cellular availability of this molecule [ 67 ].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In the same experimental setup, free BBR inhibited both planktonic and sessile populations, although at significantly higher levels, i.e., ≥125 μg/mL, compared to that accomplished by the BBR-loaded nanoparticles. The need of higher doses of free BBR might suggest the relevance of antibacterial surface-mediated mechanisms as observed before [ 63 ] which may be further supported by the low cellular availability of this molecule [ 67 ].…”
Section: Resultsmentioning
confidence: 87%
“…As such, planktonic E. faecalis and C. albicans were highly susceptible to BBR-loaded nanoparticles. BBR is reported to act via multiple and dose-dependent mechanisms encompassing intracellular and surface effects targeting specific and/or nonspecific entities or events [ 63 ]. The high activity in the planktonic pathogens might be associated with an easy cellular diffusion of the loaded nanoparticles with subsequent BBR release accomplishing inhibitory effects in microbial intracellular key mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Ding L et al 72 discovered that perfluorocarbon nanoemulsions, compared to poly-cationic/small interfering RNA (siRNA) complexes, demonstrated a more robust inhibition of pancreatic tumor growth due to the enhanced permeability and retention (EPR) effect, suggesting a promising future in the controlled therapy of pancreatic cancer.③Improved Patient Compliance: The liquid form of nanoemulsions facilitates multiple administration routes, including oral, intravenous, and topical applications. Niu Z et al 73 found that nanoemulsion-based delivery of Coenzyme Q10 showed 1.8 to 2.8 times higher bioavailability when administered orally, compared to other mediums, highlighting the potential of nanoemulsions as oral drug carriers (refer to Figure 2 ).④Taste Masking: Nanoemulsions can conceal the bitter taste of oils and drugs, making them more palatable when used as oral drug carriers. 71 ⑤Stability: Nanoemulsions are less prone to issues like flocculation, creaming, and sedimentation.…”
Section: Fundamental Principles Of Nanomedicine Drug Delivery Systemsmentioning
confidence: 99%